Optimalisasi Pemulihan Fisik Ibu Pasca Persalinan melalui Edukasi Perawatan Diri di Puskesmas Kembang Jepara - Evita Aurilia Nardina; Ratih Kumala Dewi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
The puerperium is a critical phase for postpartum mothers that requires special attention to prevent complications. However, awareness of the importance of self-care during this period remains limited, particularly in rural areas such as the working area of Puskesmas Kembang in Jepara. This community service initiative aimed to empower postpartum mothers by enhancing their knowledge and skills in self-care and physical recovery. The approach included interactive education using video media, health talks, group discussions, hands-on demonstrations, and the involvement of family members as key supporters. A total of 20 postpartum mothers and 10 family companions participated in the program. Evaluation through pre- and post-tests revealed significant improvements in knowledge across various aspects of postpartum care, including perineal hygiene, balanced nutrition, early detection of danger signs, and the role of family support. This program proved effective and has the potential to be replicated in other rural settings with similar conditions.